Estudio comparativo de estructuras de educación y atención a la infancia en siete países: Australia, Bélgica, Brasil, Canadá, Cuba, Francia y Perú - Vargas D’Uniam, Jessica (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
A comparative study of educational structures that receive children less thansix years old in seven countries: Australia, Brazil, Belgium, Canada, Cuba,France and PeruThis investigation comprises a comparative study of educational structures that receive children under six years old in seven countries: Australia, Brazil, Belgium, Canada, Cuba, France and Peru.The goal of this research is identify and analyze the educational structures that receive children under six years old. This analysis displays the mechanisms thatthey develop as an answer to their characteristics and particular needs.The analysis of the results conclude that the organization of the educational structures addressed to service little children, depends on various factors (i.e. social, economic, cultural, geographical, etcétera), and can be configured in a different way than the services and programs of education, ultimately responding to the characteristics and needs of children, their families and their community.Keywords: Early-childhood education, educational pre-school structures, preschool institutions.

La investigación comprende la comparación de estructuras educativas de atención a los niños menores de seis años en siete países: Australia, Bélgica, Brasil, Canadá, Cuba, Francia y Perú.El interés por el tema surge por la necesidad de identificar y de analizar las estructuras educativas que atienden a los niños menores de seis años, a fin de conocer los mecanismos que desarrollan para responder a sus características y necesidades particulares.El análisis de los datos permitió concluir que la organización de las estructuras educativas destinadas a la atención de los niños pequeños depende de diversos factores (sociales, económicos, culturales, geográficos, etcétera) y que puedenconfigurar de manera diferente los servicios y programas de educación, a fin de responder a las características y a las necesidades de los niños, de sus familias y de la comunidad.
Keywords: Educación Infantil; Estructuras Educativas Preescolares; Instituciones Preescolares; Early-Childhood Education; Educational Pre-School Structures; Preschool Institutions; https://purl.org/pe-repo/ocde/ford#5.03.00